Thoracoscopic Patch Repair of Congenital Diaphragmatic Hernia in a Neonate using Spiral Tacks: A Case Report - Mario A Riquelme; Carlos D Guajardo; Marco A Juarez-Parra; Rodolfo A Elizondo; Julio C Cortinas (EL-Med-Pub, 2015)
We present a case of congenital diaphragmatic hernia that was successfully treated with spi-ral tacks using thoracoscopy. A newborn female was diagnosed with a diaphragmatic hernia at 20 weeks of gestation. The defect was surgically repaired by thoracoscopy and primary closure. On postoperative day 25, she developed respiratory distress. Chest x-ray showed a recurrence and was taken to the OR for surgical repair with spiral tacks.